Anti-Staphylococcal and Antifungal Substances Produced By Endospore-Forming Bacilli - Oliveira V. F., Abreu Y. J. L., Fleming L. R., Nascimento J. S. (Journal of Applied Pharmaceutical Science)
Some bacteria and fungi are related to deterioration and also transmission of foodborne diseases, emphasizing the need to search new substances that may act in the treatment and prevention of the illnesses transmitted by food. Strains from genus Bacillus produce a variety of substances with inhibitory activity that range from antibiotics to bacteriocins. In this work, three strains, identified as B. pasteurii (Pes1) and B. insolitus (Mam2 and Ame3) presented inhibitory action against staphylococcal strains isolated from food. Out of the 33 strains tested, 31 (94.0%) were inhibited by at least one of three main Bacillus producer strains, being most of them inhibited by strain Pes1, that also was able to inhibit filamentous fungi related to food spoilage. The antimicrobial substances produced by Pes1, Mam2 and Ame3 showed to be resistant to proteolytic enzymes, suggesting these substances have not an active proteinaceous compound, as typical bacteriocins. New studies are being performed to extract and characterize these antimicrobial agents to evaluate their potential application in biological control of microorganisms related to spoilage food and foodborne diseases.
Keywords: antimicrobial substances, antifungal, anti-staphylococcal, biological control application, endospore-forming bacilli.